Pathogenesis of premature coronary artery disease: Focus on risk factors and genetic variants - Haiming Wang; Zifan Liu; Junjie Shao; Min Jiang; Xuechun Lu; Lejian Lin; Lin Wang; Qiang Xu; Haomin Zhang; Xin Li; Jingjing Zhou; Yundai Chen; et al. (Genes and Diseases, 2022)
The development of premature coronary artery disease (PCAD) is dependent on both genetic predisposition and traditional risk factors. Strategies for unraveling the genetic basis of PCAD have evolved with the advent of modern technologies. Genome-wide association studies (GWASs) have identified a considerable number of common genetic variants that are associated with PCAD. Most of these genetic variants are attributable to lipid and blood pressure-related single-nucleotide polymorphisms (SNPs). The genetic variants that predispose individuals to developing PCAD may depend on race and ethnicity. Some characteristic genetic variants have been identified in Chinese populations. Although translating this genetic knowledge into clinical applications is still challenging, these genetic variants can be used for CAD phenotype identification, genetic prediction and therapy. In this article we will provide a comprehensive review of genetic variants detected by GWASs that are predicted to contribute to the development of PCAD. We will highlight recent findings regarding CAD-related genetic variants in Chinese populations and discuss the potential clinical utility of genetic variants for preventing and managing PCAD.